THE EVOLUTION OF ECOLOGICAL POLICY WITH THE REPUBLIC OF SERBIA AS AN EXAMPLE - Midić, Nataša (Political Review, 2023)
With the goal of drawing out lessons from the past development of environmental policy in the Republic of Serbia, this paper will use a historically, functional, and theoretical analysis method to identify shortcomings, as well as the starting advances in the evolution of this branch of political science in our country. The analysis covers the period from the 80s of the 20th century and the first steps in the development of environmental policy in Serbia as the former republic of the Socialist Federal Republic of Yugoslavia, through institutional development within the Federal Republic of Yugoslavia and later Serbia and Montenegro, all the way to modern developments in the Republic of Serbia. By looking at the historical retrospective, this paper provides an answer to the question of whether the Republic of Serbia is on the right path when it comes to the development of environmental policy. Bearing in mind that Serbia has been a candidate for membership in the European Union since 2014, special attention during the analysis is devoted to the period from then until the present in order to notice the influence of the European Union on the development of environmental policy in Serbia. Such influence is definitely noticeable, given that domestic legislation is largely harmonized with the legislation of the European Union. However, what is missing is the implementation of existing laws and inspection and judicial supervision over the application of those laws. Apart from the shortcomings in the implementation of those laws, it was also noticed that there is a problem with involving the public in the creation and implementation of the environmental policy. Given the fact that the Constitution itself foresees that, in addition to the state, citizens are also responsible for a healthy environment, they must be included in the processes related to environmental protection. Insufficient transparency in connection with projects that have an impact on the environment leads to dissatisfaction among citizens and non-governmental organizations, and this dissatisfaction later often turns into protests. Instead, a dialogue must be the only way of mutual cooperation between state authorities and non-governmental organizations and citizens. When environmental protection laws are fully implemented, and citizens are involved in the creation and implementation of environmental policy, then we can talk about the right path for the evolution of the environmental policy in Serbia. Until then, the impression remains that the harmonization of domestic legislation with the legislation of the European Union is only an attempt to flatter the Union and that in practice it has no other outcome.
Keywords: environmental policy; Republic of Serbia; development of environmental policy; environmental protection; institutional framework; European union; Chapter 27